A raw coal composite inhibitor and its preparation method and application
By using raw coal composite resistors with composite hydrogel-loaded chemical resistors in coal, the problem of poor effect of single resistors in the prior art is solved, and a better coal spontaneous combustion inhibition effect is achieved, combining physics The synergistic effect of cooling and chemical inhibition, and through the characteristics of biodegradable materials, a long-term slow release of coal has been achieved.
Patent Information
- Application Number
- CN202211465753.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-11-22
AI Technical Summary
In the prior art, a single physical flame retardant or chemical barrier agent is not ideal in preventing coal spontaneous combustion, and its performance needs to be improved.
A raw coal composite inhibitor is used, which consists of a composite hydrogel and a chemical inhibitor aqueous solution. The composite hydrogel is loaded with a chemical inhibitor solution, which improves the prevention of self-ignition of coal through physical cooling and chemical inhibition. effect.
By loading chemical inhibitors with composite hydrogels, the stability and inhibition effect of chemical inhibitors are improved. At the same time, the solvent water in the hydrogel plays a physical cooling effect, which significantly improves the effect of preventing coal spontaneous combustion and through biological The characteristics of degraded materials achieve long-term slow release to prevent spontaneous combustion of coal.
Smart Images

Figure CN115926813B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of flame retardants, and in particular relates to a raw coal composite inhibitor and a preparation method and application thereof. Background Art
[0002] Coal undergoes physical and chemical adsorption with oxygen, and then a coal-oxygen reaction occurs, leading to spontaneous combustion of coal. The reason is that the more active oxygen-containing groups in coal are easily oxidized and release heat, especially for high-volatile raw coal, which is more likely to undergo oxidation and exothermic reaction due to its high activity.
[0003] At present, an important means to prevent coal spontaneous combustion is inhibitors. Inhibitors can be divided into physical inhibitors and chemical inhibitors according to their mechanism of hindering coal spontaneous combustion. Physical flame retardants include salt inhibitors, colloidal inhibitors, foam inhibitors (inert gases), polymer inhibitors and other types. Their mechanism is to achieve the inhibitory effect through physical cooling. Physical inhibitors have various defects. Most physical inhibitors do not have a long-lasting inhibitory effect through physical cooling, and some physical inhibitors will undergo decomposition reactions and release heat, thereby increasing the temperature and promoting coal spontaneous combustion. Chemical inhibitors include antioxidants, ionic liquids and other types. Their mechanism is to change the surface properties of coal (such as surface functional group properties) to reduce the reactivity and reaction rate of oxygen and coal, so as to slow down the surface low-temperature oxidation process. However, chemical flame retardants also have unstable chemical properties and are easily decomposed during storage and transportation, resulting in inconvenience in storage and transportation. Therefore, the current effect of a single physical flame retardant or chemical inhibitor in preventing coal spontaneous combustion is not ideal, and its performance needs to be improved. Summary of the invention
[0004] In view of this, the present application provides a raw coal composite inhibitor and its preparation method and application, which are used to solve the technical problem that the single physical flame retardant or chemical inhibitor in the prior art is not effective enough in preventing coal spontaneous combustion and the performance needs to be improved.
[0005] In a first aspect, the present application provides a raw coal composite inhibitor, including a composite hydrogel and a chemical inhibitor aqueous solution;
[0006] The composite hydrogel is loaded with the chemical inhibitor solution.
[0007] Preferably, the mass ratio of the solvent water to the raw coal composite inhibitor in the chemical inhibitor aqueous solution is 90-99%:100.
[0008] High water content can fully improve the physical cooling effect of the inhibitor, and can dissolve more chemical inhibitors, thereby improving the effect of the chemical inhibitor in inhibiting the low-temperature oxidation reaction of coal.
[0009] Preferably, the inhibitor solute in the chemical inhibitor aqueous solution includes polyethylene glycol, sodium hypophosphite and vitamin C.
[0010] Preferably, the composition of the composite highly absorbent gel includes, by weight, 10 parts by weight of sodium carboxymethyl cellulose, 0.5 to 10 parts by weight of polyethylene glycol, 0.5 to 10 parts by weight of sodium hypophosphite, and 0.5 to 25 parts by weight of vitamin C.
[0011] Preferably, the composition of the composite highly absorbent gel includes, by weight, 10 parts by weight of sodium carboxymethyl cellulose, 6 parts by weight of polyethylene glycol, 6 parts by weight of sodium hypophosphite, and 6 parts by weight of vitamin C.
[0012] It should be noted that a specific mass ratio of chemical inhibitors is beneficial to improving the effect of inhibiting the low-temperature oxidation reaction of coal.
[0013] Preferably, the composite highly absorbent gel comprises sodium carboxymethyl cellulose, sodium polyacrylate and aluminum chloride.
[0014] Preferably, the composite highly absorbent gel comprises, by weight, 10 parts by weight of sodium carboxymethyl cellulose, 0.1 to 5 parts by weight of sodium polyacrylate, and 1 to 9 parts by weight of aluminum chloride.
[0015] Preferably, calculated by weight, the composition of the composite highly absorbent gel includes 10 parts by weight of sodium carboxymethyl cellulose, 1 part by weight of sodium polyacrylate and 4 parts by weight of aluminum chloride.
[0016] The second aspect of the present application provides a method for preparing a raw coal composite inhibitor, comprising the steps of:
[0017] Step 1, respectively preparing an aqueous solution containing solutes of sodium carboxymethyl cellulose and sodium polyacrylate (solution 1) and an aqueous solution containing solutes of polyethylene glycol, sodium hypophosphite, vitamin C and aluminum chloride (solution 2);
[0018] Step 2, adding solution 2 to solution 1, stirring fully, to obtain a raw coal composite inhibitor;
[0019] In step 2, the speed of the stirring reaction is not less than 600 r / min, the time is not less than 15 min, and the temperature is 20-30° C.
[0020] It should be noted that the present application also provides a method for preparing a raw coal composite inhibitor, which includes first preparing a viscous solution of sodium carboxymethyl cellulose and sodium polyacrylate. The preparation method can be selected to dissolve sodium carboxymethyl cellulose and sodium polyacrylate in water, and then add an aqueous solution containing a cross-linking agent and a chemical inhibitor to the viscous solution for stirring reaction. As the stirring reaction proceeds, the sodium carboxymethyl cellulose and sodium polyacrylate are cross-linked into a three-dimensional network structure and the chemical inhibitor and its aqueous solution are wrapped in the three-dimensional network structure to obtain a raw coal composite inhibitor.
[0021] The third aspect of the present application provides an application of a raw coal composite inhibitor in a coal pile;
[0022] The application in the coal pile is specifically: mixing the raw coal composite inhibitor with the coal pile.
[0023] It should be noted that the raw coal composite inhibitor provided in the present application is in a viscous liquid state, and after being mixed with coal particles in a coal pile, the effect of preventing coal spontaneous combustion is more excellent.
[0024] In summary, the present application provides a raw coal composite inhibitor and a preparation method and application thereof, wherein the raw coal composite inhibitor comprises a composite highly hydrophilic gel and a chemical inhibitor aqueous solution, and the composite highly hydrophilic gel loads the chemical inhibitor solution; wherein, since the composite highly hydrophilic gel is a three-dimensional network structure, and the sodium carboxymethyl cellulose constituting the three-dimensional network structure contains a large number of water-absorbing groups, the solvent water and the solute chemical inhibitor in the chemical inhibitor solution can be wrapped in the three-dimensional structure of the hydrogel, and the solute chemical inhibitor in the chemical inhibitor solution is wrapped in the three-dimensional structure of the hydrogel, thereby improving the chemical stability and slowing down the chemical inhibitor during the storage and operation process. The effect of inhibiting the low-temperature oxidation reaction of coal due to decomposition is weakened, thereby improving the inhibitory effect of the chemical inhibitor. At the same time, the solvent water in the chemical inhibitor solution in the hydrogel can also play a physical cooling and fire extinguishing role, so that the raw coal composite inhibitor provided by the present application has a superior effect in preventing coal spontaneous combustion, and the composite highly absorbent gel as a carrier is a biodegradable material, so that the solvent water and solute chemical inhibitor in the carrier chemical inhibitor solution can be slowly released to play a long-term effect of preventing coal spontaneous combustion, thereby solving the technical problem that the effect of a single physical flame retardant or chemical inhibitor in preventing coal spontaneous combustion in the prior art is not superior enough and the performance needs to be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the specific implementation of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the specific implementation or the prior art description. Obviously, the drawings described below are some implementations of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 This is a flow chart for preparing the raw coal composite inhibitor provided in the examples of the present application. DETAILED DESCRIPTION
[0027] The present application provides a raw coal composite inhibitor and a preparation method and application thereof, which are used to solve the problem that the effect of a single physical flame retardant or chemical inhibitor in preventing coal spontaneous combustion in the prior art is not ideal.
[0028] The technical solution of the present application will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0029] Example 1
[0030] Example 1 of the present application is a raw coal composite inhibitor, the components of the composite inhibitor include a composite hydrogel and a chemical inhibitor aqueous solution, and the three-dimensional cross-linked network structure of the composite hydrogel is loaded with the chemical inhibitor aqueous solution.
[0031] Among them, since the three-dimensional cross-linked network structure of the composite hydrogel is loaded with an aqueous solution of a chemical inhibitor, the chemical inhibitor is not easy to decompose during storage and transportation, and the performance of the chemical inhibitor in inhibiting low coal oxidation reactions is effectively maintained. At the same time, the solvent water in the aqueous solution of the chemical inhibitor loaded by the composite hydrogel also plays a role in physical cooling and fire extinguishing. The physical and chemical inhibition work synergistically, greatly improving the effect of a single physical flame retardant or chemical inhibitor in preventing coal spontaneous combustion. At the same time, since the hydrogel is a biodegradable material, when it is sprayed on the coal pile, it will slowly release the chemical inhibitor solution it carries, and play a long-term effect in preventing coal spontaneous combustion.
[0032] At the same time, for the components of the composite hydrogel, the present application prefers sodium carboxymethyl cellulose, sodium polyacrylate and aluminum chloride. Aluminum chloride as a cross-linking agent can promote the cross-linking of sodium carboxymethyl cellulose and sodium polyacrylate into a three-dimensional network structure to form a hydrogel, and the rich hydrophilic groups contained in sodium carboxymethyl cellulose and sodium polyacrylate also provide a basis for the loaded water content. The loaded water content in the raw coal composite inhibitor provided by the present application can reach 90-99%; and for the types of chemical inhibitors, the present application prefers polyethylene glycol, sodium hypophosphite and vitamin C, polyethylene glycol, sodium hypophosphite and vitamin C. C can play the role of inhibiting the low-temperature oxidation reaction of coal, which is specifically reflected in the ability to reduce the content of active groups such as methyl, methylene, carboxyl and hydroxyl groups on the surface of raw coal, thereby inhibiting the low-temperature oxidation reaction of coal and playing the role of preventing coal from spontaneous combustion; for the proportion of each component in the raw coal composite inhibitor, this application prefers 10 parts by mass of sodium carboxymethyl cellulose, 1 part by mass of sodium polyacrylate, 4 parts by mass of aluminum chloride and 6 parts by mass of polyethylene glycol, 6 parts by mass of sodium hypophosphite, and 6 parts by mass of vitamin C. Under such a proportion, the content of active groups such as methyl, methylene, carboxyl and hydroxyl groups on the surface of raw coal is the best. Of course, other types of hydrogels and their loaded chemical inhibitors are used to prevent the spontaneous combustion of coal, which belongs to the same inventive concept as this patent and is within the scope of protection of this patent.
[0033] Example 2
[0034] Example 2 of the present application provides a method for preparing a raw coal composite inhibitor, the preparation method comprising the steps of:
[0035] Step 1: prepare a viscous aqueous solution containing sodium carboxymethyl cellulose and sodium polyacrylate and a mixed solution containing solutes polyethylene glycol, sodium hypophosphite, vitamin C and aluminum chloride.
[0036] Calculated by mass, 10 parts by mass of sodium carboxymethyl cellulose and 1 part by mass of sodium polyacrylate are dissolved in water to prepare a viscous aqueous solution containing sodium carboxymethyl cellulose and sodium polyacrylate, and then 6 parts by mass of polyethylene glycol, 6 parts by mass of sodium hypophosphite, 6 parts by mass of vitamin C and 4 parts by mass of aluminum chloride are dissolved in water to obtain a mixed solution containing solutes of polyethylene glycol, sodium hypophosphite, vitamin C and aluminum chloride.
[0037] Step 2: preparing raw coal composite inhibitor.
[0038] A viscous solution containing sodium carboxymethyl cellulose and sodium polyacrylate and a mixed solution containing solute polyethylene glycol, sodium hypophosphite, vitamin C and aluminum chloride are stirred to react. The speed of the stirring reaction is not less than 600 r / min, the time is not less than 15 minutes, and the temperature is 20-30°C, so that the sodium carboxymethyl cellulose and sodium polyacrylate are cross-linked and chemical inhibitors such as polyethylene glycol, sodium hypophosphite, vitamin C, etc. are wrapped to prepare a raw coal composite inhibitor.
[0039] It should be noted that, for the preparation method in step 1, the present application preferably first prepares a viscous solution containing sodium carboxymethyl cellulose and sodium polyacrylate, and then prepares a mixed solution containing solutes polyethylene glycol, sodium hypophosphite, vitamin C and aluminum chloride. This is because the viscous solution containing sodium carboxymethyl cellulose and sodium polyacrylate has good stability and a long storage time.
[0040] Example 3
[0041] Example 3 of the present application provides a method for preparing a raw coal composite inhibitor, which differs from Example 2 in that:
[0042] Step 1, calculated by mass, dissolving 10 parts by mass of sodium carboxymethyl cellulose and 1 part by mass of sodium polyacrylate in water to prepare a viscous aqueous solution containing sodium carboxymethyl cellulose and sodium polyacrylate, and then dissolving 6 parts by mass of polyethylene glycol, 4 parts by mass of sodium hypophosphite, 4 parts by mass of vitamin C and 4 parts by mass of aluminum chloride in water to obtain a mixed solution containing solutes of polyethylene glycol, sodium hypophosphite, vitamin C and aluminum chloride.
[0043] Example 4
[0044] Example 4 of the present application provides a method for preparing a raw coal composite inhibitor, which differs from Example 2 in that:
[0045] Step 1, calculated by mass, dissolve 10 parts by mass of sodium carboxymethyl cellulose and 1 part by mass of sodium polyacrylate in water to prepare a viscous aqueous solution containing sodium carboxymethyl cellulose and sodium polyacrylate, and then dissolve 4 parts by mass of polyethylene glycol, 6 parts by mass of sodium hypophosphite, 8 parts by mass of vitamin C and 4 parts by mass of aluminum chloride in water to obtain a mixed solution containing solutes of polyethylene glycol, sodium hypophosphite, vitamin C and aluminum chloride.
[0046] Example 5
[0047] Example 5 of the present application provides a method for preparing a raw coal composite inhibitor, which differs from Example 2 in that:
[0048] Step 1, calculated by mass, dissolve 10 parts by mass of sodium carboxymethyl cellulose and 1 part by mass of sodium polyacrylate in water to prepare a viscous aqueous solution containing sodium carboxymethyl cellulose and sodium polyacrylate, and then dissolve 8 parts by mass of polyethylene glycol, 4 parts by mass of sodium hypophosphite, 6 parts by mass of vitamin C and 4 parts by mass of aluminum chloride in water to obtain a mixed solution containing solutes of polyethylene glycol, sodium hypophosphite, vitamin C and aluminum chloride.
[0049] Example 6
[0050] Example 6 of the present application provides a method for preparing a raw coal composite inhibitor, which differs from Example 2 in that:
[0051] Step 1, calculated by mass, dissolve 10 parts by mass of sodium carboxymethyl cellulose and 1 part by mass of sodium polyacrylate in water to prepare a viscous aqueous solution containing sodium carboxymethyl cellulose and sodium polyacrylate, and then dissolve 2 parts by mass of polyethylene glycol, 8 parts by mass of sodium hypophosphite, 8 parts by mass of vitamin C and 4 parts by mass of aluminum chloride in water to obtain a mixed solution containing solutes of polyethylene glycol, sodium hypophosphite, vitamin C and aluminum chloride.
[0052] Test Example 1
[0053] This test example conducts performance testing and flame retardant mechanism verification on the raw coal composite inhibitor, vitamin C and commercially available JPZ-1 liquid inhibitor provided in Examples 2-6, in order to compare the differences in the performance of preventing coal spontaneous combustion among the raw coal composite inhibitor, vitamin C and commercially available JPZ-1 liquid inhibitor provided in Examples 2-6.
[0054] Among them, the raw coal composite inhibitor performance test includes:
[0055] 1) The coal from Zhanjiang Power Plant was crushed in the air, and the coal with a particle size of 10-40 mesh was selected. The coal was placed in a vacuum drying oven, and the temperature was set to 70°C and the drying time was 3 hours. A coal sample with a mass of 3 kg was obtained and placed in a dryer for standby use;
[0056] 2) Fix the temperature sensor on the iron plate with iron wire, pour 300g of coal sample into the center of the iron plate so that the sensor is located in the center of the coal pile;
[0057] 3) Place the iron plate in the drying oven and set a certain temperature. When the oven reaches the specified temperature, turn on the temperature recorder and record the data;
[0058] 4) The test period was 50 hours; the application of flame retardant, the application method and the temperature inside the coal pile under different ambient temperatures were tested. The results are shown in Table 1
[0059] Table 1 Temperature rise of coal pile within 50 hours under different factors
[0060]
[0061] It can be seen from Table 1 that after the raw coal composite inhibitor provided by the present application is mixed with the inside of the coal pile, the raw coal composite inhibitor can delay the heating time of the coal peak temperature, and the coal peak temperature can be reduced as the mixing content of the raw coal composite inhibitor increases. Moreover, compared with internal mixing, the effect of crusting the surface of the raw coal composite inhibitor in delaying the heating time of the coal peak temperature and reducing the coal peak temperature is slightly lower.
[0062] In order to further explore the mechanism of spontaneous combustion of coal placed in the raw coal composite inhibitor provided in this application, this test example also conducts a mechanism exploration experiment. The test method includes two steps: sample preparation and testing:
[0063] The sample preparation steps include: collecting coal samples from mining areas where spontaneous combustion of coal is serious, sealing them and sending them to the laboratory, and then preparing them into 10-40 mesh coal samples according to "Coal Sample Preparation Method GB474-2008"; then vacuum storing the original coal samples without any treatment for future use; using a portion of the untreated raw coal as a test sample, and spraying a portion of the raw coal on its surface with the raw coal composite inhibitor provided in Examples 2-6, vitamin C, and the commercially available JPZ-1 liquid inhibitor as a test sample.
[0064] The test steps include: according to the test steps described in "Coal Oxidation Kinetics Theory and Application" published by Science Press, the distribution and content of groups in different coals are measured by Fourier transform infrared spectrometer, and the crossover point temperature during the oxidation and heating process of different coals is measured by coal spontaneous combustion tendency oxidation kinetics measuring instrument and the resistance rate is calculated. The results are shown in Table 1.
[0065] Table 1 is the test data of the raw coal provided in Examples 2-6 before and after the raw coal surface was sprayed with commercially available JPZ-1 liquid inhibitor, vitamin C and composite inhibitor.
[0066]
[0067]
[0068] Table 1
[0069] It can be seen from Table 1 that the content of active groups such as methyl, methylene, carboxyl and hydroxyl in the untreated raw coal is high, the intersection temperature is low, and the coal sample is prone to spontaneous combustion. The content of active groups such as methyl, methylene, carboxyl and hydroxyl in the coal sample treated with JPM-1 inhibitor and vitamin C is reduced, but vitamin C reduces the intersection temperature, which may be caused by the thermal decomposition of vitamin C. Therefore, the effect of vitamin C in preventing coal spontaneous combustion is not as good as that of JPM-1 inhibitor; further, after the coal sample is surface-treated with the raw coal composite inhibitor provided in Example 2-6, the content of active groups such as methyl, methylene, carboxyl and hydroxyl in the coal sample is greatly reduced, and the intersection temperature is increased, indicating that the chemical inhibitor provided in the present application can effectively prevent coal spontaneous combustion. In addition, compared with the raw coal, the methyl / methylene content of the coal sample after surface treatment with the raw coal composite inhibitor provided in Example 2 is reduced by 54%, the hydroxyl content is reduced by 40%, the carboxyl content is reduced by 15%, and the intersection temperature is increased by 11.9°C, indicating that the raw coal composite inhibitor provided in Example 2 has the best effect in preventing coal spontaneous combustion.
[0070] Furthermore, since the chemical inhibitor for reducing active groups such as methyl, methylene, carboxyl and hydroxyl provided in the present application is loaded in the hydrogel, it can play a long-term effect of removing active groups such as methyl, methylene, carboxyl and hydroxyl, and the chemical inhibitor and its aqueous solution in the present application are loaded in the hydrogel, the solvent water in the chemical inhibitor solution in the hydrogel can also play a physical cooling and fire extinguishing role, so that the raw coal composite inhibitor provided in the present application has an excellent effect of preventing coal spontaneous combustion, and the composite highly absorbent gel as a carrier is a biodegradable material, so that the solvent water and the solute chemical inhibitor in the carrier chemical inhibitor solution can be slowly released, and the effect of preventing coal spontaneous combustion can be played for a long time.
[0071] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.
Claims
1. Application of raw coal composite inhibitor in coal pile, It is characterized by: The application in the coal pile is specifically as follows: mixing the raw coal composite inhibitor with the coal pile; The preparation method of the raw coal composite inhibitor comprises the steps of: Step 1, calculated by mass, dissolving 10 parts by mass of sodium carboxymethyl cellulose and 1 part by mass of sodium polyacrylate in water to prepare a viscous aqueous solution containing sodium carboxymethyl cellulose and sodium polyacrylate, and then dissolving 6 parts by mass of polyethylene glycol, 6 parts by mass of sodium hypophosphite, 6 parts by mass of vitamin C and 4 parts by mass of aluminum chloride in water to obtain a mixed solution containing solutes of polyethylene glycol, sodium hypophosphite, vitamin C and aluminum chloride; Step 2, stirring the viscous aqueous solution containing sodium carboxymethyl cellulose and sodium polyacrylate and the mixed solution containing solute polyethylene glycol, sodium hypophosphite, vitamin C and aluminum chloride, the stirring reaction speed is not less than 600r / min, the time is not less than 15min, and the temperature is 20-30°C, so that the sodium carboxymethyl cellulose and sodium polyacrylate are cross-linked and the polyethylene glycol, sodium hypophosphite and vitamin C chemical inhibitors are wrapped to prepare the raw coal composite inhibitor.
Citation Information
Patent Citations
Preparation method of slow-release compound inhibitor for preventing spontaneous combustion of low-rank coal
CN108359144A